Annurca apple (M. pumila Miller cv Annurca) extracts act against stress and ageing in S. cerevisiae yeast cells - Mariarita Stirpe; Vanessa Palermo; Michele Maria Bianchi; Romano Silvestri; Claudio Falcone; Giancarlo Tenore; Ettore Novellino; Cristina Mazzoni (BMC, 2017)
Abstract Background During the past years, a number of studies have demonstrated the positive effect of apple on ageing and different diseases such as cancer, degenerative and cardiovascular diseases. The unicellular yeast Saccharomyces cerevisiae represents a simple eukaryotic model to study the effects of different compounds on lifespan. We previously demonstrated that apple extracts have anti-ageing effects in this organism because of their antioxidant properties. In particular, the effect is related to the presence in this fruit of polyphenols, which give a large contribution to the antioxidant activity of apples. Methods We we used a clonogenic assay to assess the viability and the resistance to oxidative stress of S. cerevisiae cells in the presence of Annurca apple extracts. The production of ROS and the aberrant morphology of nuclei were detected by cell staining with the fluorescent dies Dihydrorhodamine 123 and DAPI, respectively. Mitochondrial morphology was analyzed by following the localization of the mito-GFP protein into the mitochondrial matrix. Results In this study, we show that apple extracts can increase yeast lifespan, reduce the levels of reactive oxygen species and cell sensitivity to oxidative stress, and prevent nuclei and mitochondria fragmentation protecting cells from regulated cell death. Conclusions In this paper, by using the yeast S. cerevisiae as a model, we have demonstrated that Annurca extracts possess antioxidant properties thanks to which the extracts can reduce the intracellular ROS levels and have anti-apoptotic functions thus prolonging cell lifespan. These results contribute to knowledge on the effects of natural compounds on ageing and support the use of yeast as a model organism for the development of simple tests to assess the effectiveness of bioactive substances from natural sources.